Folk tradition, transition, and transformation for early childhood education - Pitri, Eliza; Michaelidou, Antonia (Frontiers in Education, 2025)
Transformation of folk culture is unavoidable when aiming to make traditional elements relevant to children today. An educational event was planned during a semester based on the above assumption, as a collaboration between the Department of Education of the University of Nicosia, Cyprus, and the Cyprus Folk Art Museum. The context of activities of two undergraduate courses was modified to make museum exhibits relevant initially to 11 student–teachers and later to 20 preschool children invited at the end of the semester to participate in activities at the museum. The student–teachers’ instructional design process was based on strategies followed by artists who pursue meaningful artmaking. These strategies—stages—include identifying and personalizing a big idea, building a knowledge base, setting boundaries, and problem-solving. Whether with a small or large deviation from the initial folk cultural experience, all participants were actively involved in activities, which were inspired by tradition and evolved to transition and transformation for an educational event.